High Heels and Low Back Pain in Young Female Students - Nadeem, Iqra (International Journal of Pathology, 2019)
Objective: Prolonged use of high-heeled shoes is considered a possible cause of low back pain in female students. The aim of study is to investigate the association between high heels and low back pain Methods: A cross-sectional survey based on a standard self-reporting questionnaire was conducted among 50 female university students (aged 18-28 years) mean 21.1 years and mean height 5.1 feet using high heels of GCU Faisalabad. Purposive sampling technique was used to. Out of 50 students wearing high heels, 28 (56%) students were suffering from low back pain. Pearson Chi-Square test was applied. Results: Statistical analysis showed significant association between high heel and LBP, p=0.001. Coefficient of contingency=0.567 indicated strength of association is intermediate. Conclusion: This study also revealed that students who wear high heels for 2 or more years suffer from a bit of lower back pain and that the height of the heel increases the incidence and the intensity of pain increases as well